2017
DOI: 10.1007/s12020-017-1433-z
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic strains and mechanistic insights for the treatment of type 2 diabetes

Abstract: A major obstacle in the evaluation of probiotic strains lays in the great number of strains, differences in detection methodology and measured outcome parameters. The understanding of further research should be directed towards the development of standardized evaluation methods to facilitate the comparison of different studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 231 publications
1
49
0
5
Order By: Relevance
“…Indeed, re- cent studies have shown that inducing symbiosis improves the clinical course of not only UC [34][35][36][37] but also IBS, [38][39][40][41] checkpoint-inhibitor-induced colitis recognized as immune-related adverse events in patients with cancer, 42 hepatic encephalopathy, 43 Parkinson' s disease, 44 and type 2 diabetes. [45][46][47][48] Conventional methods used to induce symbiosis are administration of probiotics and dietary modification including intake of abun-dant dietary fiber; however, fecal microbiota transplantation (FMT) has attracted attention as a method for dramatically altering the intestinal microbiota. FMT reportedly has the potential to induce remission in some patients with UC [49][50][51][52] and may be an effective therapeutic strategy for 5-ASA intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, re- cent studies have shown that inducing symbiosis improves the clinical course of not only UC [34][35][36][37] but also IBS, [38][39][40][41] checkpoint-inhibitor-induced colitis recognized as immune-related adverse events in patients with cancer, 42 hepatic encephalopathy, 43 Parkinson' s disease, 44 and type 2 diabetes. [45][46][47][48] Conventional methods used to induce symbiosis are administration of probiotics and dietary modification including intake of abun-dant dietary fiber; however, fecal microbiota transplantation (FMT) has attracted attention as a method for dramatically altering the intestinal microbiota. FMT reportedly has the potential to induce remission in some patients with UC [49][50][51][52] and may be an effective therapeutic strategy for 5-ASA intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors additionally state that the findings on HbA1c, anti-inflammatory and anti-oxidative effects of probiotics in the clinical setting remain inconsistent. Further obstacles in the evaluation of probiotic strains also lie in the great number of strains studied, and differences in the detection methodology [ 111 ]. All authors agree that the findings in their reviews still imply a need for well-designed clinical studies.…”
Section: Therapymentioning
confidence: 99%
“…Cotillard et al showed that populations with low microbial genome abundance (40%) were relatively more likely to present with pronounced dysmetabolism and low-grade inflammation (Cotillard et al, 2013). Improvement of gut microbiota with probiotics such as Lactobacillus genus (LAB) and Bifidobacteria helps prevent and treat obesity and T2D (Hampe and Roth, 2017). Probiotics may help prevent pathogen colonization by physically interfering with attachment, competing for nutrients, producing antimicrobial substances, and inactivating endotoxins (Medellin-Pena and Griffiths, 2009).…”
Section: Discussionmentioning
confidence: 99%